2015
DOI: 10.1007/s11427-015-4844-1
|View full text |Cite
|
Sign up to set email alerts
|

An update: the role of Nephrin inside and outside the kidney

Abstract: Nephrin is a key molecule in podocytes to maintain normal slit diaphragm structure. Nephin interacts with many other podocyte and slit diaphragm protein and also mediates important cell signaling pathways in podocytes. Loss of nephrin during the development leads to the congenital nephrotic syndrome in children. Reduction of nephrin expression is often observed in adult kidney diseases including diabetic nephropathy and HIV-associated nephropathy. The critical role of nephrin has been confirmed by different an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 88 publications
0
16
0
Order By: Relevance
“…Podocytes play a vital role in the prevention of glomerular protein leakage during physiological and pathological processes through formation of slit diaphragm [3740]. Clinical reports have demonstrated that smoking worsens the chronic kidney diseases, and enhances proteinuria [212].…”
Section: Discussionmentioning
confidence: 99%
“…Podocytes play a vital role in the prevention of glomerular protein leakage during physiological and pathological processes through formation of slit diaphragm [3740]. Clinical reports have demonstrated that smoking worsens the chronic kidney diseases, and enhances proteinuria [212].…”
Section: Discussionmentioning
confidence: 99%
“…Other resident glomerular cells may have more significant roles in the activation of T cells around the glomeruli. Recent studies have indicated that podocytes from parietal epithelial cells were the predominant cellular components of crescents (Appel et al, 2009); these podocytes function as local professional antigen-presenting cells in the kidney (Goldwich et al, 2013) and may destroy its structure (Li et al, 2015). Further studies are required to determine the mechanisms of interaction between T cells and podocytes to elucidate the activation of CD4 + cells in the kidney in situ.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests the importance of nephrin in the process of glomerular filtration as a structural component of the slit diaphragm. Nephrin is exclusively expressed by podocytes but also may be expressed in brain, lymphoid tissue, heart, testis, placenta and β cells of the Langerhan's islets of the pancreas [6]. NPHS1 gene is located on chromosome 19 (19q13.1), organized in 29 exons [7].…”
Section: Nephrin -(Nph) Structure and Functionmentioning
confidence: 99%